In the Company of Trees: Honoring Our Connection to the Sacred Power, Beauty, and Wisdom of Trees - Andrea Sarubbi Fereshteh (Adams Media, 2019)
ascinating facts, trivia, and stories celebrating nature and the magnificent life of trees and their invaluable place in our lives, including beautiful, full-color photographs throughout. When was the last time you spent time outside? The space between your front door and your car doesn't count. Nature holds incredible power to soothe our spirits, calm our minds, and open us up to creativity, if we can unplug long enough to step away from our screens and embrace it. And while they say you can't see the forest for the trees, they play perhaps the leading role in our enjoyment of the outdoors. In the Company of Trees helps you rediscover your own connection to the world outside, with over 195 quotes, facts, and stories honoring trees from across the world and in our own back yards alike. Inviting, full-color photos of sun-dappled forests and tree-filled hikes throughout will inspire you to do some forest-bathing of your own and embrace the healing power of nature.